(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
A retrospective review of the innovation process with its advantages, as well as the challenges in the conditions of Industry 4.0 in the Republic of Bulgaria. The emphasis is on digitalization and the strategy for its implementa-tion, as part of the national strategy for increasing the competitiveness of production and the economy.